A study on Pipeline Inspection Gauge (PIG) Flow Parameters in Small Size Pipe - Mohamad Norzuhri, Basirun (2013)
Pipeline inspection gauge or known from its acronym as PIG was basically a tool or a device that was inserted into a pipeline with the purpose of cleaning or pipeline inspection. There were different types of pigs for different use in pipeline. The most basic form and most frequently used of pig is for cleaning purpose of pipeline. There are other types of pig that was known as smart pig. Smart pig can do more than just cleaning. They can inspect the physical condition of the pipe. The main objectives of this research are to study the flow of natural gas through different types of pigs of different worn out percentage ranging from 20%, 15% and 10% from initial diameter and varied gas flow velocity from lowest to highest allowable to find the most effective types of pigs for cleaning purpose. Other than that the purpose of this research paper was to analyzed hydrates effect on natural gas flow in pipeline by studying the complex behavior of gas flow through pipeline (Velocity, Pressure, and Turbulent) using CFD modeling. In order to get the result, simulation was performed by using Computational Fluid Dynamic (CFD) software namely Fluent and Gambit. Volume meshing in GAMBIT is very important part before doing simulation in FLUENT as a solver. The model simulation helps further understanding of the variables change in form of type of PIG used and effect of hydrate to velocity, pressure and turbulent intensity in natural gas pipeline flow.